Branch Retinal Artery Occlusion after Percutaneous Coronary Intervention - Tommaso La Macchia; Remo Albiero; Tommaso Invernizzi; Giorgia Ceravolo; Ida Ceravolo (Case Reports in Cardiology)
We report a case of branch retinal artery occlusion (BRAO) that occurred after percutaneous coronary intervention (PCI). A 59-year-old man with no other previous diseases presented visual acuity deterioration in the left eye 24 hours after PCI. Fundus examination revealed ischemia at the temporal branch of the retinal artery associated with inner layer edema. Prompt treatment was performed with ocular digital massage and paracentesis of the anterior chamber. However, at discharge, the patient had a persistent visual loss with a central scotoma that persisted at 35-day follow-up without improvement of the visual acuity. The patient did not suffer from any other systemic complications. Retinal infarction should be considered a potential complication of PCI. Patients and health care providers should be aware of any visual signs. Permanent visual disability can be prevented by immediate diagnosis and prompt intervention.